Enhanced cognitive control over task-irrelevant emotional distractors in generalized anxiety disorder versus obsessive-compulsive disorder. (May 2019) - Hallion, Lauren S.; Tolin, David F.; Diefenbach, Gretchen J.
Highlights: Adults with GAD showed enhanced cognitive control over negative distractors. Findings were specific to GAD versus clinical status (OCD) or trait worry. Trait worry predicted better cognitive control in GAD participants only. Findings are broadly consistent with emotional avoidance models of GAD. Abstract: Generalized anxiety disorder (GAD) is defined in part by excessive and uncontrollable worry. However, little is known about cognitive control abilities in adults with GAD. The present study examined cognitive control over negative and neutral material in a mixed clinical sample of adults with GAD and/or obsessive-compulsive disorder and a comparison healthy control sample. Participants completed a novel emotional variant of the AX-CPT (eAX-CPT) to index proactive and reactive cognitive control in the presence of negative and neutral distractor stimuli. Participants with GAD demonstrated enhanced cognitive control specifically over negative emotional distractors, relative to neutral distractors (within-subjects) and relative to OCD and controls (between-subjects). Findings were specific to GAD versus trait worry; however, higher trait worry predicted better cognitive control in GAD only. These findings are inconsistent with deficit-based cognitive models of GAD and may be better accounted for by models that conceptualize worry as an intentional (albeit maladaptive) cognitive control or emotion regulation strategy that is actively maintained by individuals with GAD in order to avoid engaging with more distressing emotional information.